Micellar drug delivery platform from diblock copolymers - Kavak, Nehir. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
The main role of chemotherapeutic agents is killing the fast growing cells. Thus, they damage fast growing helathy cells like bone marrow as well. This harm can be prevented by modifying the existing chemotherapeutic agents that are already in clinical use to provide their accumulation into tumor. In this thesis, preparation of polymers sensitive to two different stimuli and the demonstration of their sensitivity and functionality were investigated. The synthesis of polymers are both redox- and hydrolysis-sensitive. The prepared block copolymers were functionalized by active drug molecules. All obtained structures were characterized via size exclusion chromatography and nuclear magnetic resonance. The formation of micellar structures from these block copolymers were studied via dynamic light scattering.
Keywords: Micelles.; Chemotherapy.